The NKG2D/NKG2DL axis in the crosstalk between lymphoid and myeloid cells in health and disease - Stojanovic, Ana; Correia, Margareta; Cerwenka, Adelheid (Frontiers in immunology, 2018)
Natural killer group 2, member D (NKG2D) receptor is a type II transmembrane protein expressed by both innate and adaptive immune cells, including Natural Killer (NK) cells, CD8+ T cells, iNKT cells, gdT cells and some CD4+ T cells under certain pathological conditions. NKG2D is an activating NK receptor that induces cytotoxicity and production of cytokines by effector cells and supports their proliferation and survival upon engagement with its ligands. In both innate and T cell populations, NKG2D can co-stimulate responses induced by other receptors, such as TCR in T cells or NKp46 in NK cells. NKG2D ligands (NKG2DLs) are remarkably diverse. Initially, NKG2DL expression was typically attributed to stressed, infected or transformed cells, thus signaling "dysregulated-self". However, many reports indicated their expression under homeostatic conditions, usually in the context of cell activation and/or proliferation. Myeloid cells, including macrophages and dendritic cells, are among the first cells sensing and responding to pathogens and tissue damage. By secreting a plethora of soluble mediators, by presenting antigens to T cells and by expressing co-stimulatory molecules, myeloid cells play vital roles in inducing and supporting responses of other immune cells in lymphoid organs and tissues. When activated, both macrophages and dendritic cells upregulate NKG2DLs, thereby enabling them with additional mechanisms for regulating lymphocyte responses. In this review, we will focus on the expression of NKG2D by innate and adaptive lymphocytes, the regulation of NKG2DL expression on myeloid cells and the contribution of the NKG2D/NKG2DL axis to the crosstalk of myeloid cells with NKG2D-expressing lymphocytes. In addition, we will highlight pathophysiological conditions associated with NKG2D/NKG2DL dysregulation and discuss the putative involvement of the NKG2D/NKG2DL axis in the lymphocyte/myeloid cell crosstalk in these diseases.